Protective Efficacy of Coccidial Common Antigen Glyceraldehyde 3-Phosphate Dehydrogenase (GAPDH) against Challenge with Three Eimeria Species - Tian, Lu; Li, Wenyu; Huang, Xinmei; Tian, Di; Liu, Jianhua; Yang, Xinchao; Liu, Lianrui; Yan, Ruofeng; Xu, Lixin; Li, Xiangrui; Song, Xiaokai (Frontiers in Microbiology, 2017)
Coccidiosis is an intestinal disorder of poultry and often caused by simultaneous infections of several Eimeria species. GAPDH is one of the immunogenic common antigens among Eimeria tenella, E. acervulina and E. maxima identified in our previous study. The present study was performed to further evaluate its immunogenicity and protective efficacy. The genes of GAPDH cloned from E. acervulina and E. maxima were named as EaGAPDH and EmGAPDH respectively. The immunogenicity of recombinant proteins of EaGAPDH and EmGAPDH were analyzed by Western blot. The transcription and expression of pVAX-EaGAPDH and pVAX-EmGAPDH in the injected muscles were detected by reverse transcription PCR (RT-PCR) and Western blot respectively. GAPDH-induced changes of T lymphocytes subpopulation, cytokines production and antibody were determined using flow cytometry, quantitative real-time PCR (qPCR) and ELISA respectively. Finally, the protective efficacies of pVAX-EaGAPDH and pVAX-EmGAPDH were evaluated by vaccination and challenge experiments. The results revealed that the recombinant GAPDH proteins reacted with the corresponding chicken antisera. The EaGAPDH genes were successfully transcribed and expressed in the injected muscles. Vaccination with pVAX-EaGAPDH and pVAX-EmGAPDH significantly increased the proportion of CD4+ and CD8+ T lymphocytes, the cytokines productions of IFN-γ, IL-2, IL-4 et al., and IgG antibody levels compared to controls. The vaccination increased the weight gains, decreased the oocyst outputs, alleviate the enteric lesions compared to controls, and induced moderate anti-coccidial index (ACI). In conclusion, the coccidal common antigen of GAPDH induced significant humoral and cellular immune response and effective protection against E. tenella, E. acervulina, E. maxima and mixed infection of the 3 Eimeria species.